Extreme Marine Heatwaves Alter Kelp Forest Community Near Its Equatorward Distribution Limit - Arafeh-Dalmau, Nur; Montaño-Moctezuma, Gabriela; Martínez, José A.; Beas-Luna, Rodrigo; Schoeman, David S.; Torres-Moye, Guillermo (Frontiers in Marine Science, 2019)
Climate change is increasing the frequency and severity of marine heatwaves. A recent extreme warming event (2014-2016) of unprecedented magnitude and duration in the California Current System allowed us to evaluate the response of the kelp forest community near its southern (warm) distribution limit. We obtained sea surface temperatures for the northern Pacific of Baja California, Mexico, and collected kelp forest community data at three islands, before and after the warming event. The warming was the most intense and persistent event observed to date, with low-pass anomalies 1°C warmer than the previous extremes during the 1982-1984 and 1997-1998 El Niños. The period between 2014-2017 accounted for ~50% of marine heatwaves days in the past 37 years, with the highest maximum temperature intensities peaking at 5.9°C above average temperatures for the period. We found significant declines in the number of Macrocystis pyrifera individuals, except at the northernmost island, and corresponding declines in the number of fronds per kelp individual. We also found significant changes in the community structure associated with the kelp beds: half of the fish and invertebrate species disappeared after the marine heatwaves, species with warmer affinities appeared or increased their abundance, and introduced algae, previously absent, appeared at all islands. Changes in subcanopy and understory algal assemblages were also evident; however, the response varied among islands. These results suggest that the effect of global warming can be more apparent in sensitive species, such as sessile invertebrates, and that warming-related impacts have the potential to facilitate the establishment of tropical and invasive species.